FEEDBACK STRATEGIES: AN EFFORT TO ENHANCE THE CRITICAL THINKING SKILLS OF DAF-LEARNERS IN INDONESIA - Wijayati, Primardiana Hermilia; Ardiyani, Dewi Kartika; Hidayat, Edy (International Journal of Education, 2022)
Critical thinking has become one of the main education goals in this 21st century as the trend in the global market also requires graduates to be able to apply critical thinking skills to work settings. This study aims to describe the strategy of providing feedback to improve the critical thinking skills of German as a foreign language (GFL) learners in Indonesia. The research data were collected through observations and interviews with German students and lecturers at Universitas Negeri Malang, Indonesia, and presented descriptively qualitatively with observation and interview instruments. The results showed that asking questions to students, providing comments, encouraging output, and giving praise are the feedback strategies that can improve students' critical thinking skills. Lecturers provide several questions that lead them to think and answer these questions. The questions should be given to all students in the class so that students gradually are encouraged to be more active. Through those feedback strategies, learners are triggered to memorize, understand, apply, analyze, reformulate, and evaluate the learned materials. All those strategies are implemented to lead the students to better critical thinking skills. It is recommended that lecturers apply more types of feedback so that students have more opportunities to improve their language skills.